CRISPR/Cas9 Targeted Editing of Genes Associated With Fungal Susceptibility in Vitis vinifera L. cv. Thompson Seedless Using Geminivirus-Derived Replicons - Olivares, Felipe; Loyola, Rodrigo; Olmedo, Blanca; Miccono, María de los Ángeles; Aguirre, Carlos; Vergara, Ricardo; Riquelme, Danae; Madrid, Gabriela; Plantat, Philippe; Mora, Roxana; Espinoza, Daniel; Prieto, Humberto (Frontiers in Plant Science, 2021)
The woody nature of grapevine (Vitis vinifera L.) has hindered the development of efficient genome editing (GE) strategies to improve this species. The lack of highly-efficient gene transfer techniques, combined with the use of multicellular explants such as somatic embryos are additional technical handicaps to GE in the vine. The inclusion of DNA virus-based replicons in regular T-DNA vectors can enhance the expression of CRISPR/Cas9 elements, thus enabling the use of these multicellular explants as starting material. In this study we used Bean yellow dwarf virus (BeYDV)-derived replicon vectors to express the editing reagents in vivo and to evaluate their editing capability on individuals derived from Agrobacterium-mediated gene transfer experiments of ‘Thompson Seedless’ somatic embryos. Preliminary assays using a BeYDV-derived vector for Green fluorescent protein gene expression demonstrated marker visualization in embryos for up to 33 days post infiltration. A universal BeYDV-based vector (pGMV-U) was assembled to produce all CRISPR/Cas9 components with up to four independent guide RNA (gRNA) expression cassettes. With a focus on fungal tolerance, we used gRNA pairs to address significantly large deletions of putative grape susceptibility genes including AUXIN INDUCED IN ROOT CULTURE 12 (VviAIR12), the SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTER 4 (VviSWEET4), the LESION INITIATION 2 (VviLIN2), and the DIMERIZATION PARTNER-E2F-LIKE 1 (VviDEL1). Editing functionality of gRNA pairs in pGMV-U was evaluated by grapevine leaf agroinfiltration assays, thus enabling longer-term embryo transformations. These latter experiments allowed for the establishment of greenhouse individuals exhibiting the double-cut edited status for all targeted genes under different allele-editing conditions. After approximately 18 months, these materials led to preliminary evaluation considering their tolerance behavior for Erysiphe necator and Botrytis cinerea. Assays have shown promising results regarding E. necator tolerance in the case of a VviDEL1 double-cut gene edited line for which we have also established a non-transgenic status.